Performance of GGBS Cement Concrete under Natural Carbonation and Accelerated Carbonation Exposure - Jun Zhao; Eskinder Desta Shumuye; Zike Wang; Gashaw Assefa Bezabih (Journal of Engineering)
One of the primary problems related to reinforced concrete structures is carbonation of concrete. In many cases, depth of carbonation on reinforced concrete structures is used to evaluate concrete service life. Factors that can substantially affect carbonation resistance of concrete are temperature, relative humidity, cement composition, concentration of external aggressive agents, quality of concrete, and depth of concrete cover. This paper investigates the effect of varying the proportions of blended Portland cement (ordinary Portland cement (OPC) and ground granulated blast-furnace slag (GGBS)) on mechanical and microstructural properties of concrete exposed to two different CO2 exposure conditions. Concrete cubes cast with OPC, and various percentages of GGBS (0%, 30%, 50%, and 70%) were subjected to natural (indoor) and accelerated carbonation exposure. The aim of this paper is to present the research findings and authenticate the literature results of carbonation by using GGBS cement in partial replacement of OPC. The concretes with OPC are compared to concretes with various percentages of GGBS, to assess the carbonation depth as well as rate of carbonation of GGBS-based concretes, under both accelerated carbonation and natural carbonation exposure conditions. Even though GGBS cement increases the carbonation depth, the results are not the same with different GGBS replacement percentages. A correlation is made between concrete samples exposed to 15 ± 2% carbon dioxide (CO2) concentration and those exposed to natural CO2 concentration. The results reveal that the products formed by carbonation are similar under both exposure conditions. The experimental tests also revealed that GGBS cement concrete has a lower carbonation resistance than OPC concrete, due to the consumption of portlandite by the pozzolanic reaction. The combination of 70% OPC and 30% GGBS behaved well enough with respect to accelerated carbonation exposure, the depth of carbonation being roughly equivalent to that of control group (100% OPC). The results also show that rate of carbonation becomes more sensitive as the percentage of GGBS replacement increases (binder ratio), rather than duration of curing. Concretes exposed to natural carbonation (indoor) achieved lower carbonation rates than those exposed to accelerated carbonation.